2009
DOI: 10.1108/13590790910993744
|View full text |Cite
|
Sign up to set email alerts
|

Control of insurance fraud in Nigeria: an exploratory study (case study)

Abstract: Purpose -Insurance fraud as a global economic problem threatens the financial strength of insurers and threatens the survival of the insurance institution. The purpose of this paper is to explore the magnitude of the problem including the industry's and regulatory authority's responses in tackling the menace in Nigeria. The paper is motivated by the recent effort on the part of the Nigerian regulatory authority to strengthen the sector through consolidation. Such renewed vigour on part of Nigeria is geared tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Conversely, others acknowledge the peace of mind and financial security it offers during emergencies, as highlighted in Insureds' Perception towards Insurance Services (Maltby et al, 2023). Distrust towards insurance companies due to perceived claim avoidance can also be a factor, potentially stemming from past experiences or negative media portrayals (Olalekan & Rasheed, 2009).). Xu et al (2018) further emphasizes that socioeconomic background and cultural attitudes towards risk significantly influence these perceptions.…”
Section: Original Research Articlementioning
confidence: 99%
“…Conversely, others acknowledge the peace of mind and financial security it offers during emergencies, as highlighted in Insureds' Perception towards Insurance Services (Maltby et al, 2023). Distrust towards insurance companies due to perceived claim avoidance can also be a factor, potentially stemming from past experiences or negative media portrayals (Olalekan & Rasheed, 2009).). Xu et al (2018) further emphasizes that socioeconomic background and cultural attitudes towards risk significantly influence these perceptions.…”
Section: Original Research Articlementioning
confidence: 99%
“…So far, the integration of sophisticated systems is still in the banking sector. Tajudeen & Abdur (2009) [3], who conducted a study in Nigeria, showed that the indecisive attitude of the insurance industry supervisory authority that began with unclear sanctions could lead to economic crime.…”
Section: Integrated Surveillancementioning
confidence: 99%
“…Insurance fraud is a global economic problem that threatens companies and the insurance industry [3]. According to Hayirsever (2020) [4], insurance fraud not only affects insurance companies, policyholders, but also the insurance industry as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Micro factors that affect the financial stability of companies include corporate governance (Lassoued, 2018), financial performance (Elbadry, 2016;Rashid, Yousaf & Khaleequzzaman, 2017), human resources performance (Djafri, Noordin & Mohammed, 2018;Piaralal et al, 2016), market control (Husin & Rahman, 2016;Rashid, Yousaf & Khaleequzzaman, 2017), audit opinion (Foster & Zurada, 2013) and excellent service (Piaralal et al, 2016). Meanwhile, macro factors that affect financial stability are political stability (Ozili, 2018), government regulations and policies (Kay, 2018;Berkem, 2014), level of corruption (Korbi & Bougatef, 2017;Ozili, 2018), government supervision (Kobayashi, 2017;Yusuf & Babalola, 2009), level of competition (Ozili, 2018) and level of productivity or unemployment (Din, Regupathi & Abu-Bakar, 2017).…”
Section: Previous Researchesmentioning
confidence: 99%